2017
DOI: 10.1111/acel.12616
|View full text |Cite|
|
Sign up to set email alerts
|

Akt2 ablation prolongs life span and improves myocardial contractile function with adaptive cardiac remodeling: role of Sirt1‐mediated autophagy regulation

Abstract: SummaryAging is accompanied with unfavorable geometric and functional changes in the heart involving dysregulation of Akt and autophagy. This study examined the impact of Akt2 ablation on life span and cardiac aging as well as the mechanisms involved with a focus on autophagy and mitochondrial integrity. Cardiac geometry, contractile, and intracellular Ca2+ properties were evaluated using echocardiography, IonOptix® edge‐detection and fura‐2 techniques. Levels of Sirt1, mitochondrial integrity, autophagy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 47 publications
3
79
0
Order By: Relevance
“…Consistent with these functions, autophagy constitutes a stress adaptation to avoid cardiomyocyte death, although massive autophagy activation may be detrimental for the heart under certain stress conditions. It is important that during the aging process, cardiac autophagy is progressively suppressed (Ren, Sowers, & Zhang, ; Shirakabe et al, ); thus, downregulating autophagy may underlie the progression of cardiac aging (Linton, Gurney, Sengstock, Mentzer, & Gottlieb, ; Ren et al, ). Age‐related pathologies and the aging process itself are accompanied by impaired protein quality control, dysfunctional protein accumulation, and proteostasis imbalance, all of which contribute to increased susceptibility to stress (Sciarretta et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these functions, autophagy constitutes a stress adaptation to avoid cardiomyocyte death, although massive autophagy activation may be detrimental for the heart under certain stress conditions. It is important that during the aging process, cardiac autophagy is progressively suppressed (Ren, Sowers, & Zhang, ; Shirakabe et al, ); thus, downregulating autophagy may underlie the progression of cardiac aging (Linton, Gurney, Sengstock, Mentzer, & Gottlieb, ; Ren et al, ). Age‐related pathologies and the aging process itself are accompanied by impaired protein quality control, dysfunctional protein accumulation, and proteostasis imbalance, all of which contribute to increased susceptibility to stress (Sciarretta et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other groups also reported the function of AKT in aging. AKT2 ablation prolonged lifespan and improved cardiac aging through restored FOXO 1‐related autophagy and mitochondrial integrity (Ren et al, 2017), and chronic AKT activation accentuated aging‐induced cardiac hypertrophy and myocardial contractile dysfunction through a loss of autophagic regulation (Hua et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 has a wide range of targets, including the transcription factor forkhead box class O (FOXO) 1, which is tightly associated with autophagy induction . SIRT1 can regulate autophagy by deacetylating and activating FOXO . Our previous work indicated that metformin inhibits the in vitro expression of inflammatory cytokines and activation of nuclear factor‐κB induced by high glucose in rat glomerular mesangial cells.…”
Section: Introductionmentioning
confidence: 99%